Code Switching in the Language Classroom: Perceptions and Practices of Tertiary Level Teachers - Choudhury, M. (University of Jaffna, 2025)
Code switching has become a common phenomenon in L2 classrooms. Most bilingual Language teachers switch codes in the classroom. Ghaderi et al write that, “code-switching, despite the historical debate, serves various purposes in language classrooms, including facilitating comprehension, managing the class, and enhancing learner engagement.”. This study aimed to explore the practice of code-switching by English language teachers at the tertiary level, firstly, to identify the reasons for which they switch codes, secondly, to find out the extent to which code switching is practiced by them, and, finally, to ascertain the type of code-switching that takes place in the classroom. Five tertiary level language teachers teaching foundation level English to Freshers in a private university of Dhaka, Bangladesh were chosen using purposive sampling. The data were collected through classroom observations and semi-structured interviews. Three classes of each sample were observed to document the extent to which each participant switched codes and the type of code switching they practiced. The semi-structured interviews were designed to find out the teachers’ perceptions of why they switched codes. Data were analyzed using Miles and Huberman’s three step analysis process i.e. data reduction, data display and lastly drawing conclusions. The findings of the study have implications for language teachers who can make more efficacious use of code-switching if it is done with a more critically deliberative approach.
Keywords: Code-switching; English language classroom; Teacher perception; Teacher practice